the Data Warehouse Design for the Bank X with Inmon Approach - Lanang Bagus Amertha; Rukmi Sari Hartati; Made Sudarma (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
Various activities related to financial transactions such as the process of deposit and loan funds require the role of the Bank. Along with a large number of customer needs in current technological developments, the banking industry is undergoing many changes. The products offered by the Bank are becoming more diverse. Customers needs for services offered by banks are becoming increasingly high for example internet banking needs. Banks require high data storage so that the bank's business processes can run efficiently. High data requirements by banks also require ease of exchanging data. One concept that can be applied is Data Warehouse. There are various approaches in developing Data Warehouse, one of which is Inmon. This study aims to build a database design from Bank X Data Warehouse with the Inmon approach. The results of the design of the Data Warehouse Bank X database design consists of three fact tables, namely loan fact, saving fact, and portfolio fact, and two data marts, namely loans and saving.